Peer Assessment-based Digital Literacy, EFL Students’ Reading Competency, and Engagement - Lailiyah, Leni; Ratminingsih, Ni Made; Utami, IGA Lokita Purnamika; Artini, Luh Putu; Padmadewi, Ni Nyoman; Marsakawati, Ni Putu Era (Journal of Education Reseach and Evaluation, 2022)
In the 21st century, students must master digital literacy. During the COVID-19 pandemic, many students could still not use online learning support facilities. It has an impact on decreasing reading competence and student engagement. This study aims to determine the effect of peer assessment-based digital literacy on reading competency and engagement of EFL students during the post-COVID-19 pandemic. This research utilized a quasi-experimental design. A total of 10 groups of students participated in this study. Two groups of students were selected using cluster random sampling; 30 participants were assigned to the experiment, and 30 were assigned to the control group. The data instruments used two post-tests and a questionnaire. The dataset was statistically analyzed using One-way ANOVA and MANOVA, with assistance from SPSS version 26.0. The findings of this study implied that there was a significant effect of peer assessment-based digital literacy on the reading competency of EFL students; and there was a significant effect of peer assessment-based digital literacy on the EFL students' engagement. There is a simultaneous effect of peer assessment-based digital literacy on EFL students' reading competency and engagement. This study found that peer assessment-based digital literacy is one of the best ways to improve EFL students' reading competency and engagement. It is suggested that more research be done on this topic, not just on how well students read, but also on how motivated students are to learn, how students and parents see each other, how involved parents are, and what factors help and hinder students.